(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The issues of improving the layout of the drives of the working body of seed cleaning machines are considered namely the layout of the two-shaft unbalanced vibration exciters of the directed action of the exciting force with an electric motor placed in the system of the oscillating part of the separator. It is shown that the proposed schemes for regulating the angle of oscillation of the working body of the separators are currently imperfect and in most separators are structurally complex. The paper proposes two layout schemes for the drive of the working body of seed cleaning machines with the placement of the electric motor on the end or side wall of the vibratory exciter depending on the layout of the working body of the seed cleaning machine itself. For both layout options dependencies are proposed with the help of which the scheme and shape of the layout of the drive sled are calculated which allows simplifying the procedure for adjusting the directionality of the oscillations of the working body of seed cleaning machines.